PENGARUH USAHA KECIL MENENGAH DAN SEKTOR PARIWISATA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN PROBOLINGGO - Rahman, Failur (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The GRDP (Gross Regional Domestic Product) of Probolinggo Regency has been impacted by the pandemic's influence on the number of tourists. If the drop in economic growth in the Probolinggo district is contrasted with the decline in the national economy, it becomes clear that the decline in economic growth in the Probolinggo district is smaller. Based on a comparison of processed data, the Probolinggo district's economic growth decreased by -2.12% while the nation's economic growth decreased by -4.25%. In comparison to other national tourism priorities like Bali, which saw a fall in economic growth of 11.06%, the area that is part of the national tourism priority has experienced a comparatively minor decline in economic growth. Because the Probolinggo district is categorized as experiencing a relatively smaller decline in economic growth when compared to Bali and several other national priority tourist areas, it can be said that this phenomenon is unique to study in the regency that has an international tourist area and is a national priority tourism area, namely Mount Bromo. In order to ascertain how the tourism industry and SMEs affect economic growth in the Probolinggo district, this research was carried out. Regression analysis using time series data is the technique employed. The results of the regression analysis reveal that the expansion of the MSME and tourist industries in the Probolinggo district is significantly influenced. However, only the MSME sector and not the tourism industry has a substantial and partial impact on the GRDP. Therefore, it can be concluded that the decline in economic growth in Probolinggo district, which is smaller than the decline in national economic growth, and in regions that have national priority tourism areas can be proven, namely that the tourism sector only influences the MSME sector simultaneously on GRDP but not partially.